A Synthetic Carrier of Nucleic Acids Structured as a Neutral Phospholipid Envelope Tightly Assembled on Polyplex Surface. Issue 6 (24th January 2020) - Xue, Yonger; Feng, Jia; Liu, Yilei; Che, Junyi; Bai, Guang; Dong, Xiaotao; Wu, Fei; Jin, Tuo
Abstract: Synthetic carriers of nucleic acids remain inefficient for practical applications due to their insufficient functions as compared with viral vectors developed by evolution. Here, a synthetic carrier is designed to structurally mimic lentivirus, a widely‐used viral vector in therapeutic developments, for its neutral phospholipid membrane tightly anchored on the surface of a packed nucleic acid core. Unlike the reported lipopolyplexes of which the surface membrane around the nucleic acid core is formed from charged lipids, the stable attachment of the neutral lipids to each polyplex core in the present system is achieved through preadsorbed micelles of multicarboxyl amphiphilic molecules as lipid bilayer anchors. The adsorbed micelles are under a tension of deformation due to the electrostatic attraction of the head groups to the cationic surface and their "thermodynamic responsibility" to cover the hydrophobic tails in water. When liposomes of neutral phospholipids approach, the hydrophobic tail groups of the adsorbed micelles may insert into the lipid bilayer matrix to induce them to fuse around polyplex and relieve the thermodynamic tension. The formed neutral phospholipid membrane may encapsulate the polyplex core stably, prevent siRNA from prephagocytic leaking and degrading, and immobilize functional agents with increased capacity. Abstract : This report demonstrates a method to assemble a stable neutral phospholipid membrane on a polyplex surface to protect the nucleic acid core and immobilize functional components on the synthetic vector. Multi‐carboxyl amphiphilic molecules may adsorb on the surface of the polyplex tightly in the form of micelles and induce liposomes of neutral phospholipids to fuse and form a surface‐anchored membrane thermodynamically.